Defining the Simulation Technician Role. Issue 5 (October 2015) - Bailey, Rachel; Taylor, Regina G.; FitzGerald, Michael R.; Kerrey, Benjamin T.; LeMaster, Thomas; Geis, Gary L.
<x xml:space="preserve">Abstract</x> Introduction In health care simulation, simulation technicians perform multiple tasks to support various educational offerings. Technician responsibilities and the tasks that accompany them seem to vary between centers. The objectives were to identify the range and frequency of tasks that technicians perform and to determine if there is a correspondence between what technicians do and what they feel their responsibilities should be. We hypothesized that there is a core set of responsibilities and tasks for the technician position regardless of background, experience, and type of simulation center. Methods We conducted a prospective, survey-based study of individuals currently functioning in a simulation technician role in a simulation center. This survey was designed internally and piloted within 3 academic simulation centers. Potential respondents were identified through a national mailing list, and the survey was distributed electronically during a 3-week period. Results A survey request was sent to 280 potential participants, 136 (49%) responded, and 73 met inclusion criteria. Five core tasks were identified as follows: equipment setup and breakdown, programming scenarios into software, operation of software during simulation, audiovisual support for courses, and on-site simulator maintenance. Independent of background before they were hired, technicians felt unprepared for their role once taking the position. Formal training was identified as a need; however, the majority of technicians felt experience over time was the main contributor toward developing knowledge and skills within their role. Conclusions This study represents a first step in defining the technician role within simulation-based education and supports the need for the development of a formal job description to allow recruitment, development, and certification.